2014
DOI: 10.1161/circinterventions.114.001533
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes of Pulmonary Arteries Treated by Balloon Pulmonary Angioplasty in a Patient With Chronic Thromboembolic Pulmonary Hypertension

Abstract: A 41-year-old man was referred to our hospital for the treatment of chronic thromboembolic pulmonary hypertension (CTEPH). On admission, he was in World Health Organization functional class III. Right heart catheterization demonstrated that pulmonary arterial pressure (systolic/diastolic/mean) was 140/42/71 mm Hg, cardiac index was 1.6 L/min/m2 and pulmonary vascular resistance was 1663 dyn ·s·cm -5 . The patient had severe pulmonary hypertension and was considered inoperable because of peripheral organized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…It is essential that physicians performing angioplasty and other 14 We need to understand the outcomes of severe complications (such as dissection or perforation of pulmonary arteries) and how to manage these complications when performing BPA for CTEPH. 21,22 In conclusion, we reclassified thromboembolic lesions of CTEPH into 5 types by modifying the widely used previous angiographic classification and demonstrated that the outcome and complication rate of BPA are closely related to the location and morphology of the thromboembolic lesion. This novel classification might be helpful in developing strategies to perform BPA in patients with CTEPH who are unsuitable for PEA.…”
Section: Discussionmentioning
confidence: 87%
“…It is essential that physicians performing angioplasty and other 14 We need to understand the outcomes of severe complications (such as dissection or perforation of pulmonary arteries) and how to manage these complications when performing BPA for CTEPH. 21,22 In conclusion, we reclassified thromboembolic lesions of CTEPH into 5 types by modifying the widely used previous angiographic classification and demonstrated that the outcome and complication rate of BPA are closely related to the location and morphology of the thromboembolic lesion. This novel classification might be helpful in developing strategies to perform BPA in patients with CTEPH who are unsuitable for PEA.…”
Section: Discussionmentioning
confidence: 87%
“…In the second, the media of the PA was dissected by angioplasty and the organized thrombi were forced to one side, leaving a larger pseudo-lumen with formation of a new intimal layer. 40 …”
Section: Balloon Pulmonary Angioplastymentioning
confidence: 99%
“…Vessel diameter spontaneously expanded over time and ultimately the pressure gradient across the lesion was eliminated. Given our previous observation of vessel wall dissection caused by BPA, 31 we speculate that pressure overload in the pulmonary artery with partial detachment of an organized thrombus may cause dilatation of the artery distal to the occlusion. For this reason, we recently began to use small balloons at the initial dilatation, increasing the diameter of dilatation at subsequent procedures, a protocol that increases safety by avoiding vascular complications.…”
Section: Bpa Indications and General Proceduresmentioning
confidence: 63%
“…In pathologically examined lesions after BPA, we found a small incision through the organized thrombus in 1 case, 30 and dissection of the tunica media with partial detachment of the organized thrombus from the vascular wall in other cases (Figure 3). 31 Thus, the thrombi were not extracted from inside the blood vessel as in PEA, but were forced to one side to enlarge the lumen.…”
Section: Treatment Goalmentioning
confidence: 99%
See 1 more Smart Citation